Conserving transboundary wildlife migrations: recent insights from the Greater Yellowstone Ecosystem. Issue 2 (9th December 2019) - Middleton, Arthur D; Sawyer, Hall; Merkle, Jerod A; Kauffman, Matthew J; Cole, Eric K; Dewey, Sarah R; Gude, Justin A; Gustine, David D; McWhirter, Douglas E; Proffitt, Kelly M; White, PJ
Abstract : Animal migrations are ecologically, culturally, and economically important. Ungulate populations in many parts of Africa, Asia, Europe, and the Americas migrate long distances to access seasonally available resources, traversing vast landscapes in large numbers. Yet some migrations are declining, raising concerns among scientists and natural resource managers. We synthesize recent advances in ungulate migration ecology with relevance to management and policy. Using case studies from the Greater Yellowstone Ecosystem (GYE), we show how new tools can be applied to map ungulate migrations and assess threats across multiple seasonal habitats, serving as a conservation roadmap. To help conserve ungulate migrations, we also propose a transboundary science, policy, and management framework that could be adapted beyond the GYE and that encompasses the needs of multiple species. The key elements of this framework consist of more widespread mapping and assessment of migrations, improved federal and state coordination across jurisdictional lines, increased investment in private land conservation, and strong engagement of local stakeholders positioned to sustain conservation activities over the long term.